Osteosynthesis of intertrochanteric fractures by PFN and DHS – A prospective randomized comparative study - Pulin Bihari Das; Anurag Singh; Bhabani Shankar Lenka; Sunit Pani (Journal of Orthopaedics, Trauma and Rehabilitation)
Introduction: As the geriatric population increases, the incidence of intertrochanteric fractures (ITF) has also increased significantly. There are various modalities to treat these fractures. In this study our aim is to analyse outcomes of Proximal Femoral Nail (PFN) in comparison to those of Dynamic Hip Screw (DHS) for the treatment of ITF. Materials and Methods: This study was carried out during 2017–20. 150 patients of unstable ITF (AO type 31-A2, 31-A3) in elderly were randomly divided into two groups of 75 each and were treated either by DHS or PFN and were followed up regularly. Results: The results were compared between the groups and statistical analyses were performed. The results were assessed with Harris Hip Score(HHS) & Parker Palmer mobility score (PPMS) which were better in PFN group. Conclusion: PFN is a better fixation device for unstable ITF (31 A2 and 31 A3) in elderly patients.